Lactobacillus fermentum as a new inhibitor to control advanced glycation end-product formation during vinegar fermentation - Qin Li; Leibing Li; Hanjian Zhu; Fan Yang; Ke Xiao; Lin Zhang; Menglin Zhang; Yongsheng Peng; Chao Wang; Dongsheng Li; Qian Wu; Mengzhou Zhou (Food Science and Human Wellness)
The inhibitory activity of lactic acid bacteria (LAB) toward advanced glycation end-products (AGEs) during vinegar fermentation was studied, and its relationships with the substrate consumption, antioxidant capacity, total phenolic content, total flavonoid compounds, α-glucosidase, and α-amylase activity inhibition were evaluated. The vinegar was made from rice powder flour by liquid-state fermentation (LSF). The selected LAB strains were separately co-cultivated with Saccharomyces cerevisiae and Acetobacter pasteurianus 1.41 in alcoholic and acetic acid fermentation, respectively. Among 3 strains, Lactobacillus fermentum showed the strongest inhibitory effect on the formation of total fluorescent AGEs and carboxymethyl lysine (CML)/carboxyethyl lysine (CEL) in the fermentation process. The corresponding mechanisms included the acceleration of substrate consumption, improvement of antioxidant activities, and inhibition of α-glucosidase and α-amylase. In addition, the fluorescent AGEs and the CML/CEL were negatively correlated with the antioxidant activities, while the α-glucosidase and α-amylase activities were positively correlated with the total phenols and total flavonoids. Moreover, the variety of main flavor compounds increased, including esters, alcohols, phenols and acids. The results of the study support the potential use of screened LAB strains to inhibit the formation of fluorescent AGEs, CML and CEL on fermented products and in the food processing industry, without associated risks to consumers.